Blood Pressure Variability and Baroreflex Sensitivity in Premature Newborns—An Effect of Postconceptional and Gestational Age - Javorka, Kamil; Haskova, Katarina; Czippelova, Barbora; Zibolen, Mirko; Javorka, Michal (Frontiers in Pediatrics, 2021)
Introduction: Cardiovascular system is the vitally important system in the dynamical adaptation process of the newborns to the extrauterine environment. To reliably detect immaturity in the given organ system, it is crucial to study the development of the organ functions in relation to maturation process. Objectives: The objective was to determine the changes in the spontaneous short-term blood pressure variability (BPV) and baroreflex sensitivity (BRS) reflecting various aspects of cardiovascular control during the process of maturation in preterm babies and to separate effects of gestational age and postnatal age. Methods: Thirty-three prematurely born infants without any signs of cardio-respiratory disorders (gestational age: 31.8, range: 27 – 36 weeks; birth weight: 1704, range: 820 – 2730 grams) were enrolled. Continuous peripheral blood pressure signal was obtained by non-invasive volume-clamp photoplethysmography method during supine rest. The recordings of 250 continuous beat-to-beat blood pressure values were processed by spectral analysis of BPV (assessed measures: total power, low frequency and high frequency powers of systolic BPV) and BRS calculation. For each infant we also assessed systolic, diastolic and mean blood pressures, heart rate and respiratory rate. Results: With the postconceptional age, BPV measures decreased (for total power: Spearman correlation coefficient rs = -0.345, P = 0.049; for low frequency power: rs = -0.365, P = 0.037; for high frequency power rs = -0.349; P = 0.046); and BRS increased significantly (rs = 0.448, P = 0.009). The further analysis demonstrated that these effects were more attributable to gestational age than to postnatal age. BRS correlated negatively with BPV magnitude (rs = -0.479 – -0.592, P = 0.001 – 0.005). Mean blood pressure and diastolic blood pressure increased during maturation (rs = 0.517 and 0.537, P = 0.002 and 0.001, respectively) while heart rate and respiratory rate decreased (rs = -0.366 and -0.516, P = 0.036 and 0.002, respectively). Conclusion: We conclude that maturation process is accompanied by an increased involvement of baroreflex buffering of spontaneous short-term blood pressure oscillations. Gestational age plays a dominant role not only in BPV changes but also in BRS, mean blood pressure, diastolic blood pressure and heart rate changes.